Bacterial volatiles promote growth in Arabidopsis - Ryu, C.M; Farag, M.A; Hu, C.H; Reddy, M.S; Wei, H.X; Pare, P.W; Kloepper, J.W (Proceedings of the National Academy of Sciences - PNAS, 2003)
Several chemical changes in soil are associated with plant growth-promoting rhizobacteria (PGPR). Some bacterial strains directly regulate plant physiology by mimicking synthesis of plant hormones, whereas others increase mineral and nitrogen availability in the soil as a way to augment growth. Identification of bacterial chemical messengers that trigger growth promotion has been limited in part by the understanding of how plants respond to external stimuli. With an increasing appreciation of how volatile organic compounds signal plants and serve in plant defense, investigations into the role of volatile components in plant-bacterial systems now can follow. Here, we present chemical and plant-growth data showing that some PGPR release a blend of volatile components that promote growth of Arabidopsis thaliana. In particular, the volatile components 2,3-butanediol and acetoin were released exclusively from two bacterial strains that trigger the greatest level of growth promotion. Furthermore, pharmacological applications of 2,3-butanediol enhanced plant growth whereas bacterial mutants blocked in 2,3-butanediol and acetoin synthesis were devoid in this growth-promotion capacity. The demonstration that PGPR strains release different volatile blends and that plant growth is stimulated by differences in these volatile blends establishes an additional function for volatile organic compounds as signaling molecules mediating plant-microbe interactions.